THE IMPLEMENTATION OF WORDWALL GAMES IN VOCABULARY LEARNING - Nasru Ilahiyati; Zuliati Rohmah; Hamamah Hamamah (IJEE (Indonesian Journal of English Education), 2023)
ABSTRACTThis article investigates the use of online-based application "WordWall Games" as a vocabulary learning tool. The research aims to observe the participants' ability to enhance pronunciation, memorize vocabulary, and construct words into sentences. This study addresses three research questions: How is the design of WordWall games beneficial for developing students' vocabulary?; How is the application of WordWall games integrated into vocabulary teaching?; How do students acquire new vocabulary after being instructed using WordWall? To collect the data for this study, the researchers conducted direct observations involving ten students studying English Literature in Malang as participants of this study. Six game-based media were utilized, including Random Card Games, Crossword Games, True or False Tasks, Translation Tasks, Construct Word Tasks, and Anagram Tasks. The  research findings indicate that using WordWall games as a learning tool effectively improves students’ pronunciation, memorization, and sentence construction skills.ABSTRAKArtikel ini membahas penggunaan aplikasi berbasis online "WordWall games" sebagai alat pembelajaran kosakata. Penelitian ini bertujuan untuk mengobservasi kemampuan partisipan dalam meningkatkan pengucapan, menghafal, dan menyusun kata-kata menjadi kalimat. Artikel ini membahas tiga pertanyaan: 1. Bagaimana desain WordWall games bermanfaat untuk mengembangkan kosakata siswa? 2. Bagaimana penerapan WordWall games dalam pengajaran kosakata? 3. Bagaimana siswa memperoleh kosakata baru setelah diajarkan menggunakan WordWall? Peneliti melakukan observasi langsung yang melibatkan sepuluh mahasiswa yang sedang menempuh pendidikan Sastra Inggris di Malang. Enam media berbasis permainan digunakan, termasuk Random Card Games, Crossword Games, True or False Tasks, Translation Tasks, Construct Word Tasks, dan Anagram Tasks. Temuan penelitian menunjukkan bahwa penggunaan WordWall games sebagai alat pembelajaran efektif dalam meningkatkan pengucapan, penghafalan, dan kemampuan menyusun kalimat.How to Cite: Ilahiyati, N., Rohmah, Z., Hamamah. (2023). The Implementation of Wordwall Games in Vocabulary Learning. IJEE (Indonesian Journal of English Education), 10(1), 144-159. doi:10.15408/ijee.v10i1.29905.